Upaya meningkatkan kreativitas anak usia dini melalui media loose parts pada kelompok B di KB Sirojul Huda Pasuruhan Kayen Pati Tahun Pelajaran 2022/2023 - Siti Jariyah; Isna Maylani; Farah Rizkita Putri (STAI Syekh Jangkung, 2024)
This research was motivated by the low level of creativity of students at KB Sirojul Huda Pasuruhan Kayen Pati. Based on the results of activities in the pre-cycle, children's creativity is classified as low. Therefore, there is a need to improve learning that can increase students' creativity. It is hoped that the application of loose part media can be a solution to this problem. The purpose of this research is to find out the creativity of children today, describe Loose Parts Media in increasing the creativity of early childhood, explain the effectiveness of Loose Parts media in learning, and find out the results of the evaluation of increasing creativity in early childhood through Loose Parts media in group B at KB Sirojul Huda Pasuruhan Kayen Pati Academic Year 2022/2023. The research method implemented was classroom action research using the Kurt Lewin model which consists of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection. The subjects of this research were Group B children consisting of 30 students. The data collection techniques used are interviews, observation, documentation and tests.